2011
DOI: 10.1115/1.4004124
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Heat Release Distribution in Turbulent Flames by a Model Based Correction of OH* Chemiluminescence

Abstract: Imaging of OH* or CH* chemiluminescence with intensified cameras is often employed for the determination of heat release in premixed flames. Proportionalitx is commonly assumed, hut in the turbulent case this assumption is not justified. Substantial deviations from proportionality are observed, which are due to turbulence-chemistry interactions.In this study a model based correction method is presented to obtain a better approximation of the spatially resolved heat release rate of lean turbulent flames from OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
57
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 32 publications
2
57
0
Order By: Relevance
“…A good review of those can be found in Lauer et al 3 There are only few papers that compare the OH * radiation with the heat release rate in non-premixed flames. Panoutsos et al studied single nonpremixed methane-air flames numerically at atmospheric pressure and found that for this flame, the peaks of the heat release rate and the OH * radiation are close to one another.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A good review of those can be found in Lauer et al 3 There are only few papers that compare the OH * radiation with the heat release rate in non-premixed flames. Panoutsos et al studied single nonpremixed methane-air flames numerically at atmospheric pressure and found that for this flame, the peaks of the heat release rate and the OH * radiation are close to one another.…”
Section: Introductionmentioning
confidence: 98%
“…2 This theoretically defined quantity is difficult to obtain in experiments. 3 Especially under the harsh conditions in realistic liquid rocket demonstrators, where access to the combustion chamber is limited, the direct determination of the volumetric heat release rate is practically impossible.…”
Section: Introductionmentioning
confidence: 99%
“…These studies stress out the need of alternative techniques to measure heat release rate disturbances. Measurements are then often limited to flame images for qualitative analysis except in a few studies where the signal is calibrated using specific post-processing procedures to map the heat release rate on two-dimensional images [15,16]. Another limitation is that the chemiluminescence emission yields a signal integrated in the line-of-sight and it is difficult to obtain spatially resolved data without additional hypothesis on the system symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…This last signal is supposed to be proportional to the heat release rate for premixed fiâmes [19], giving access to heat release fluctuations, a crucial quantity in the understanding of combustion instabilities. In the case of partially premixed flames, several studies [20,21] have shown that the OH* emission still provides qualitative information on the heat release fluctuations, on a global point of view.…”
Section: Introductionmentioning
confidence: 99%